Penguatan Kompetensi Sosial Emosional Mahasiswa sebagai Strategi Pencegahan Konflik di Perguruan Tinggi Universitas Musamus Merauke - Nurul Uswatun Hasanah; Adela Anita; Anugerah Mulia Utami; Hermanto Tinambunan; Seven Marganda Bako; Gabriel Gloria Ohee (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study offers an in-depth examination of the role of social–emotional competence (SEC) in preventing conflict within higher education institutions, particularly in the multicultural and socioeconomically diverse region of South Papua. Universities in this region operate within a complex intersection of cultural identities, historical tensions, infrastructural limitations, and unstable digital communication, all of which contribute to heightened vulnerability to student conflict. Using an expanded systematic literature review and sociocultural contextual analysis, the study reveals that emotional regulation, empathy, social awareness, intercultural competence, and digital emotional literacy significantly contribute to reducing interpersonal, intergroup, and online conflicts among university students. The findings further indicate that SEC related initiatives in Indonesian universities remain fragmented, limiting their long-term impact on campus harmony. This study proposes a conceptual model for institutionalizing SEC within curriculum design, campus policies, faculty development, and student programming to promote sustainable conflict prevention and social cohesion in multicultural higher education settings.